2021
DOI: 10.1021/acs.jctc.1c00396
|View full text |Cite
|
Sign up to set email alerts
|

Combined Surface-Hopping, Dyson Orbital, and B-Spline Approach for the Computation of Time-Resolved Photoelectron Spectroscopy Signals: The Internal Conversion in Pyrazine

Abstract: A computational protocol for simulating time-resolved photoelectron signals of medium-sized molecules is presented. The procedure is based on a trajectory surface-hopping description of the excited-state dynamics and a combined Dyson orbital and multicenter B-spline approach for the computation of cross sections and asymmetry parameters. The accuracy of the procedure has been illustrated for the case of ultrafast internal conversion of gas-phase pyrazine excited to the 1 B 2u (ππ*) state. The simulated spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…The transient population of the dark A u state in the photophysics of pyrazine has become a controversially discussed topic in the recent literature. , While Suzuki and co-workers could not find evidence for the intermediate population of the A u state, Leone and co-workers reported detection of population in the A u state with a time delay of 200 fs . A recent computational simulation of the TRPES of pyrazine confirmed that the A u population indeed cannot be clearly distinguished from the B 3u population in TRPES . According to quantum dynamics calculations for an ab initio based three-state nine-mode model of pyrazine as well as full-dimensional ab initio quasiclassical SH simulations for pyrazine, the (diabatic) B 3u and A u states are comparably populated already after 50 fs (Figure b).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The transient population of the dark A u state in the photophysics of pyrazine has become a controversially discussed topic in the recent literature. , While Suzuki and co-workers could not find evidence for the intermediate population of the A u state, Leone and co-workers reported detection of population in the A u state with a time delay of 200 fs . A recent computational simulation of the TRPES of pyrazine confirmed that the A u population indeed cannot be clearly distinguished from the B 3u population in TRPES . According to quantum dynamics calculations for an ab initio based three-state nine-mode model of pyrazine as well as full-dimensional ab initio quasiclassical SH simulations for pyrazine, the (diabatic) B 3u and A u states are comparably populated already after 50 fs (Figure b).…”
mentioning
confidence: 93%
“…Experimentally, the photodynamics of pyrazine was studied by Suzuki and co-workers with femtosecond time-resolved photoelectron spectroscopy (TRPES) in the UV and very recently by Leone and co-workers with femtosecond X-ray absorption spectroscopy . The transient population of the dark A u state in the photophysics of pyrazine has become a controversially discussed topic in the recent literature. , While Suzuki and co-workers could not find evidence for the intermediate population of the A u state, Leone and co-workers reported detection of population in the A u state with a time delay of 200 fs . A recent computational simulation of the TRPES of pyrazine confirmed that the A u population indeed cannot be clearly distinguished from the B 3u population in TRPES .…”
mentioning
confidence: 99%
“…In this calculation, all atoms are described by a double zeta polarized basis (DZP) and the LB94 functional has been used to describe exchange and correlation effects [ 41 ]. The choice of this functional is well supported by a significant number of accurate photoionization studies performed over the years [ 42 , 43 , 44 ]. The parameters used to calculate bound and continuum orbitals expressed in the B-spline LCAO basis have been chosen to reach convergence with the lowest computational cost.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to improving the diabatic-adiabatic transformation in vMCG calculations, a possible approach for this comparison would be the computation of the diabatic populations in TSH simulations. While ways of doing this have been proposed [41,54], a systematic implementation is not yet available.…”
Section: Direct-dynamics: Butatriene and Cyclohexadienementioning
confidence: 99%